Biologic targeting in the treatment of inflammatory bowel diseases [Retraction] - Bosani M (Dove Medical Press, 2014)
Bosani M, Ardizzone S, Porro GB. Biologics: Targets and Therapy. 2009;3:77–97.This paper has been retracted after we were made aware that it contains a large amount of reused, and uncited material that was not placed within quotation marks.The following statement has been supplied by Dr Sandro Ardizzone:The review entitled "Biologic targeting in the treatment of inflammatory bowel disease" has been commissioned by this journal and published in 2009 (Matteo Bosani, Sandro Ardizzone, Gabriele Bianchi Porro. Biologics: Targets & Therapy 2009;3:77–97). The paper was written by our young coworker (Dr M Bosani). He has consulted many papers, including our previous reviews published years before. The not perfect knowledge of English language has greatly influenced the writing of the paper itself. So he saved in word file several parts of our previous papers (Ardizzone S, Bianchi Porro G. Inflammatory bowel disease: new insights into pathogenesis and treatment. J Intern Med 2002;252:475–496 – Ardizzone S, Bianchi Porro G. Biologic therapy for inflammatory bowel disease. Drugs 2005:2253–2286), and then transferred to the final paper. He was unaware as we are, of the fact that he could not reuse previously published material in other journals. The reuse of this material was made in good faith.Taking our responsibility for what happened, we intend to apologize for this inconvenience to the Editor (Dr Doris Benbrook) and Publisher (Dr Tim Hill). Moreover, for the reasons mentioned above, I consider appropriate to retract the paper itself.This retraction relates to this paper.